(untitled) (Fiep Bulletin - online, 2012)
Introduction - The dental students and professionals who provide health services are exposed to occupational hazards, especially those that manipulate biological materials. Objective - To analyze the social representations of occupational risk developed by dental students. Methodology - This is an exploratory research conducted with 64 dental students of a private college in Teresina - Piaui. The data have been produced using semi-structured interview, Alceste 4.8 software processed in the lexical analysis and done by descendant hierarchical classification. Results - are presented in four semantic classes, namely: 1 - Use of personal protective equipment by dental students, 2 - Exposure of dental students to diseases like AIDS and hepatitis, 3 - Exposure to biological hazards, through saliva and blood; 4 - Exposure to ergonomic risks, such as repetitive strain injuries. The analysis of the constituent elements such as knowledge and information in the common sense of students, led to the apprehension of the social representations of occupational hazards with an emphasis on ergonomic risks, the class to pay more, because the students and dentists to be victims of their own customs and biological hazards, that even though the class to pay less, be linked to the risk of accidents with sharps, which increase exposure to biological agents, considered the main occupational hazard. Conclusion - the prevention of occupational hazards for dental students has not yet been incorporated as a set of measures necessary for the patient and their health in the workplace to reduce the occurrence of occupational accidents and cross infections but to prevent risks ergonomic, especially for repetitive movements and may result in damage to the patient caused by work-related musculoskeletal disorders - MDRW, which is reflected in a practice with less quality.